Analysis of Development of Innovation and Competitiveness in Montenegro - Zdravko Krivokapić; Jelena Jovanović; Aleksandar Vujović; Sanja Peković; Davorin Kramar (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
This paper presents some of the results obtained during many years of work on the scientific - research projects in the field of innovation and improvement of organizational performance with aim to find an answer about Capacity for innovation of Montenegrin organizations. The paper is based on the unique database which reflects the real conditions of the Montenegrin organizations. In the paper is also analyzed report prepared by World Economic Forum (WEF) for 20142015 years about Global Competitiveness Index (GCI) for Montenegro. In accordance with that report and analysis of survey performed in Montenegrin organizations carried out by interview method, authors of the paper tried to give an answer about Capacity for innovation in Montenegro. Based on that analysis we found that Montenegrin organizations are focused on innovation but there still have a lot of spaces for improving in order to achieve higher level of Global Competitiveness Index.
Keywords: O31; 330; Innovations; Capacity for innovation; GCI; Questionnaire